2014
DOI: 10.1111/1462-2920.12364
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity and the presence of algae in halite endolithic communities are correlated to atmospheric moisture in the hyper‐arid zone of the Atacama Desert

Abstract: The Atacama Desert is one of the oldest and driest deserts in the world, and its hyper-arid core is described as 'the most barren region imaginable'. We used a combination of high-throughput sequencing and microscopy methods to characterize the endolithic microbial assemblages of halite pinnacles (salt rocks) collected in several hyper-arid areas of the desert. We found communities dominated by archaea that relied on a single phylotype of Halothece cyanobacteria for primary production. A few other phylotypes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
172
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(189 citation statements)
references
References 75 publications
17
172
0
Order By: Relevance
“…Habitats as different as the underside of quartz rocks (Azúa-Bustos et al, 2011;Cowan et al, 2011;Chan et al, 2013;de los Ríos et al, 2014;Vikram et al, 2015), sandstones (Friedmann, 1982;de la Torre et al, 2003;Pointing et al, 2009), granite boulders (Wei et al, 2015), the inside of gypsum (Dong et al, 2007;Wierzchos et al, 2011Wierzchos et al, , 2015 and halite evaporites (Wierzchos et al, 2006;Robinson et al, 2015), carbonaceous (DiRuggiero et al, 2013) and volcanic rocks Cámara et al, 2014) among others, have shown that life has found innovative ways to adapt to the extreme conditions of hyper-arid deserts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Habitats as different as the underside of quartz rocks (Azúa-Bustos et al, 2011;Cowan et al, 2011;Chan et al, 2013;de los Ríos et al, 2014;Vikram et al, 2015), sandstones (Friedmann, 1982;de la Torre et al, 2003;Pointing et al, 2009), granite boulders (Wei et al, 2015), the inside of gypsum (Dong et al, 2007;Wierzchos et al, 2011Wierzchos et al, , 2015 and halite evaporites (Wierzchos et al, 2006;Robinson et al, 2015), carbonaceous (DiRuggiero et al, 2013) and volcanic rocks Cámara et al, 2014) among others, have shown that life has found innovative ways to adapt to the extreme conditions of hyper-arid deserts.…”
Section: Introductionmentioning
confidence: 99%
“…In the Yungay area of the hyper-arid zone of the Atacama Desert, with decades between rainfall events and extremely low air relative humidity (RH; mean yr −1 values <35%), ancient halite crusts of evaporitic origin have been shown to provide sufficient moisture to sustain cryptoendolithic (within pores) microbial communities (Wierzchos et al, 2006;de los Ríos et al, 2010;Robinson et al, 2015). Another strategy for survival in this hyper-arid desert is the colonization of cracks and fissures of rock substrates, also called chasmoendolithic colonization (Dong et al, 2007;DiRuggiero et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This remarkable discovery was made inside the halite deposits that form part of the Neogene salt-encrusted playas of Atacama, also known as salares (7). Chroococcidiopsis-like cells were the only cyanobacteria found inside halite pinnacles, and phylogenetic studies revealed their close genetic affinity to the genus Halothece (5,6). The presence of this endolithic community indicates that life has found a survival strategy in the hyperarid zone of Atacama, where all other colonization strategies have failed.…”
mentioning
confidence: 97%
“…Indeed, only extremely low concentrations of microorganisms had been detected in the soils of this zone (3). However, despite the major constraint for microbial life in the desert being the scarcity of liquid water, an abundance of photosynthetic life, mainly cyanobacteria associated with heterotrophic bacteria and archaea, has recently been detected in the Atacama's hyperarid zone (4)(5)(6). This remarkable discovery was made inside the halite deposits that form part of the Neogene salt-encrusted playas of Atacama, also known as salares (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation